In Cold War skies NATO and Soviet air power, 1949-89 - Napier, Michael (Osprey Publishing, 2020)
Throughout the second half of the 20th century, international relations across the globe were dominated by the Cold War. From 1949 until the fall of the Berlin Wall in 1989, US and Soviet strategic forces were deployed across the Arctic Ocean in North America and Northern Russia, while the best-equipped armed forces that the world had ever seen faced each other directly across the 'Iron Curtain' in Europe. In Cold War Skies examines the air power of the major powers both at a strategic and at a tactical level throughout the 40 years of the Cold War. In this fascinating book, acclaimed historian Michael Napier looks at each decade of the war in turn, examining the deployment of strategic offensive and defensive forces in North America and Northern Russia as well as the situation in Europe. He details the strategic forces and land-based tactical aircraft used by the air forces of the USA, USSR, NATO, Warsaw Pact countries and the European non-aligned nations. He also describes the aircraft types in the context of the units that operated them and the roles in which they were used. The text is supported by a wide range of first-hand accounts of operational flying during the Cold War, as well as numerous high-quality images.